Preparation and in vitro characterization of chitosan nanoparticles containing Mesobuthus eupeus scorpion venom as an antigen delivery system - Mohammadpour Dounighi,N (2012)
Hydrophilic nanoparticles have been widely investigated in recent years as delivery systems for therapeutic macromolecules such as antigens. In the present study Mesobuthus eupeus venom-loaded chitosan nanoparticles were prepared via ionic gelation of tripolyphosphate (TPP) and chitosan. The optimum encapsulation efficiency (91.1%) and loading capacity (76.3%) were obtained by a chitosan concentration of 2 mg/mL, chitosan-to-TPP mass ratio of 2 and M. eupeus venom concentration of 500 µg/mL. The average nanoparticle size at optimum conditions was determined by Zetasizer (Malvern Instruments, UK). The nanoparticle size was about 370 nm (polydispersity index: 0.429) while the zeta potential was positive. Transmission electron microscope (TEM) imaging showed a spherical, smooth and almost homogenous structure for nanoparticles. Fourier transform infrared (FTIR) spectroscopy confirmed tripolyphosphoric groups of TPP linked with ammonium groups of chitosan in the nanoparticles. The in vitro release of nanoparticles showed an initial burst release of approximately 60% in the first ten hours, followed by a slow and much reduced additional release for about 60 hours. It is suggested that the chitosan nanoparticles fabricated in our study may provide a suitable alternative to traditional adjuvant systems.